Digitalization of user-oriented demand planning through Building Information Modeling (BIM). Issue 3 (November 2020) - Theißen, S; Drzymalla, J; Höper, J; Liermann, E; Wimmer, R; Meins-Becker, A; Henne, A; Kloster, N; Lambertz, M
Abstract: Digitalization is accelerating and changing much in our lifestyles and ways of working. In the construction and building sector, this phenomenon is currently gaining acceptance through the Building Information Modeling (BIM) method. As an integral planning method for improving the quality of planning, construction and operating processes, BIM requires a starting point that is defined by demand planning. This paper focuses on recording demand planning digitally and generating it autonomously for basic planning. The aim is to provide planners with a BIM model that is generated early from user-oriented needs with in-depth information and enables considering sustainable and health planning aspects in the future. As a result, BIM and the open BIM data exchange format Industry Foundation Classes (IFC) are used to create a BIM-Model (3D Model) based on user needs, which are recorded by a web application. Thereby planners will be provided with a valuable starting and orientation basis that considers important user requirements. In doing so, maximum user satisfaction and quality will be achieved. Furthermore, communication and participation of users in the planning process will be promoted.